(NmNOGOMERNYJ STATISTI^ESKIJ ANALIZ (B:s (Nu^EBNOE POSOBIE (B/s - (NgIRKO(B, (NwQ^ESLAW lEONIDOWI^s ((NkIEW (B:s (NwY]A [KOLA(B,s, 1988)
(NpREDM(B. (NUKAZ(B.: (NS(B. 318-319s
(NbIBLIOGR(B.: (NS(B. 316-317s
Keywords: (NsTATISTI^ESKIJ ANALIZs